Redesigning Tourism Potential in Supporting Local Food Culture Festivals in Papua Region - ., Fitriani; Lekatompessy, Ransta L; Tjilen, Alexander P (Journal of Ecohumanism, 2025)
The Papua region is famous for its natural beauty, art and culture. This wealth is a very good potential to be encouraged and developed to improve the welfare of the local community and local revenue. The government has so far tried to map and allocate funds for tourism needs in Papua, but there has been no significant increase in this sector. even the community feels that they do not have programs made by the government. This study aims to redesign the tourism potential analysis model in the Papua region. This research is qualitative, while to compile recommendations using the Asoca analysis method (ability, strength, opportunity, culture, intelligence) related to the tourism potential analysis mechanism model in encouraging proper cultural festival management in the Papua region. This study found that there are 19 strategic steps that can be taken, and redesigning the thinking and potential of local food tourism if it will be carried out in the Papua region is to provide a large space for the community not only to be involved but also to plan, implement and determine what potential the village has so that it can be realized into a festival, and evaluate it. Meanwhile, the position of the government is as a driver and companion for the village community. other driving elements are related agencies, universities, stakeholders (sponsors), media, communities, and security forces.